Examining the total factor productivity changing patterns in Kazakhstan: An input-output analysis - Yasmin, Tahira; El Refae, Ghaleb A.; Eletter, Shorouq; Kaba, Abdoulaye (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
The interconnectedness of sectors displays the demand for inputs and supply as a level of output in any economy. This paper addresses the Total Factor Productivity (TFP) in Kazakhstan sectors by using input-output tables during 2012-2017. The change in total sectoral production was separated into two parts: the changes in technical coefficients of intermediate inputs and the change in value-added inputs, respectively. The main findings have identified a changing pattern in sectoral performance. At the same time, the result justified that various sectors such as; petroleum, manufacturing, construction, and food processing sectors have shown increased productivity. The country highly depends on extractive industries but still has better manufacturing value-added performance. The study suggests that to combat challenges like COVID-19 and climate change, it is vital to develop human capital and diversity. With diversification and innovative measures, an economy can attain sustainable economic growth in the long term.